AB0038 Modulation of the Survival of Proinflammatory TH1 Lymphocytes by Stable Expression of MIR-148A Sponges in a Murine Model of Transfer Colitis. (9th June 2015) - Maschmeyer, P.; Zimmermann, J.; Tran, C.L.; Haftmann, C.; Rausch, B.; Riedel, R.; Herzog, S.; Chang, H.-D.; Radbruch, A.; Mashreghi, M.-F.
Abstract : Background: Proinflammatory T helper (Th) cells are critically involved in the initiation and perpetuation of chronic inflammatory diseases (CID). In these diseases, proinflammatory Th cells persist in inflamed tissues and are refractory to current immunosuppressive therapies. The molecular factors regulating the survival of proinflammatory Th cells are not fully understood. Recently, we have shown that proinflammatory Th1 cells adapt to chronic inflammation by upregulating the expression of the microRNA (miRNA, miR)-148a 1 . MiR-148a promotes the survival of proinflammatory Th1 cells by regulating the expression of the pro-apoptotic protein Bim. Memory Th cells isolated from inflamed synovia of patients with rheumatoid arthritis induce the expression of miR-148a, presumably enhancing their survival. Therefore we hypothesize, that miR-148a could represent a therapeutic target for the selective elimination of proinflammatory Th1 cells in CID. Objectives: To test the suitability of miR-148a as a therapeutic target in a preclinical murine model of transfer colitis. Methods: We have generated a retroviral based inducible miR-148a inhibitor, containing complementary binding sites for miR-148a, termed "miR-148a sponge". We transduced transgenic Th cells with the miR-148a sponge or a scrambled (scr) control sponge. Induction of sponge expression was initiated by tamoxifen treatment. Expression of miRNA sponges was detected by GFP reporter gene expression and the functionality of miR148a inhibition was determined by real-time PCR for the miR-148a target Bim. MiR-148a sponge-transduced CD4 + Th1 cells were FACS-sorted and transferred into Rag1 -/- mice. After manifestation of colitis, mice were sacrificed and T cells were re-isolated from the spleens and colons for determining their phenotype and number by FACS analysis. Results: Expression of miR-148a sponges resulted in a 2 fold increase of Bim expression in activated Th1 cells in vitro . In addition, we found reduced numbers of miR-148a-sponge expressing Th cells as compared to scr-sponge expressing Th cells in the spleens and colons of colitic mice. Finally, miR-148a sponge-expressing Th cells from spleens and colons of colitic mice showed higher levels of Bim expression per cell than scr-sponge expressing cells. Conclusions: Our data suggest that miR-148a controls the survival of pro-inflammatory Th1 cells in chronic inflammation by inhibiting Bim expression. Thus, therapeutic targeting of miR-148a probably is suitable for the selective depletion of proinflammatory Th1 cells in chronic inflammation. References: Haftmann, C. et al. miR-148a is upregulated by Twist1 and T-bet and promotes Th1-cell survival by regulating the proapoptotic gene Bim. European journal of immunology, doi:10.1002/eji.201444633 (2014). Acknowledgements: Patrick Maschmeyer is supported by EUTRAIN, a FP7 Marie Curie Initial Training Network for Early Stage Researchers funded by the European Union. Disclosure of Interest: None declared